SIRT1 alleviates hepatic ischemia-reperfusion injury via the miR-182-mediated XBP1/NLRP3 pathway - Fengwei Li; Lei Zhang; Hui Xue; Jianbing Xuan; Shu Rong; Kui Wang (Elsevier, 2021)
The hepatoprotection of histone deacetylase sirtuin 1 (SIRT1) has been identified to attenuate ischemia-reperfusion (IR)-triggered inflammation and liver damage. This study was performed to characterize the function of SIRT1 in hepatic IR injury. In in vivo assays on liver-specific knockout mice of SIRT1, we first validated the effect of SIRT1 knockout on liver damage and XBP1/NLRP3 inflammasome activation. Next, we examined whether knockdown of XBP1/NLRP3 or miR-182 agomir could reverse the effect of SIRT1 knockout. In in vitro assays, NCTC1469 cells subjected to hypoxia/reoxygenation (H/R) were transduced with small interfering RNA (siRNA)/activator of SIRT1 or miR-182 agomir to confirm the effect of SIRT1 on NCTC1469 cell behaviors as well as the regulation of miR-182 and the XBP1/NLRP3 signaling pathway. Hepatic IR injury was appreciably aggravated in SIRT1 knockout mice, and SIRT1 knockdown abolished the inhibition of XBP1/NLRP3 inflammasome activation, which was reversed by NLRP3 knockdown, XBP1 knockdown, or miR-182 agomir. Mechanistically, miR-182 expression was positively regulated by SIRT1 in hepatic IR injury in mice, and miR-182 inhibited the expression of XBP1 by binding to the 3' untranslated region (UTR) of XBP1. The histone deacetylase SIRT1 inhibits the downstream XBP1/NLRP3 inflammatory pathway by activating miR-182, thus alleviating hepatic IR injury in mice.